Data transparency regarding the implementation of European 'no net loss' biodiversity policies. (February 2018) - Bull, Joseph W.; Brauneder, Kerstin; Darbi, Marianne; Van Teeffelen, Astrid J.A.; Quétier, Fabien; Brooks, Sharon E.; Dunnett, Sebastian; Strange, Niels
Abstract: 'No net loss' (NNL) conservation policies seek to address development impacts on biodiversity. There have been no peer-reviewed multinational assessments concerning the actual implementation of NNL policies to date. Such assessments would facilitate more informed debates on the validity of NNL for conservation, but assessing implementation requires data. Here, we explore data transparency concerning NNL implementation, with four European countries providing a case study. Biodiversity offsets (offsets) are the most tangible outcome of NNL policy. Using an expert network to locate all offset datasets available within the public domain, we collated information on offset projects implemented in France, Germany, the Netherlands and Sweden. Implementation data for offsets were found to be non-transparent, but the degree of transparency varies widely by country. We discuss barriers preventing data transparency — including a perceived lack of necessity, lack of common protocols for collecting data, and a lack of resources to do so. For the data we collected we find that most offsets in Europe: are not within protected areas; involve active restoration; and, compensate for infrastructure development. The area occupied by European offsets is at least of the order 10 2 km 2 . Transparent national NNL databases are essential for meeting good practice NNL principles, but are not currently available in Europe. We discuss what such databases might require to support evaluation of NNL policy effectiveness by researchers, the conservation community and policymakers.